The Role of Human Resources Management in an Organization or Company - Yoeyong Rahsel; Miswan Gumanti (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
This research aims to explain and find out how important human resource management is for an organization or company by using the literature review method. The conclusion of this study is that human resource management has a very important role in Planning, Organizing, Human Resource Development, Directing & Controlling managerial and operational functions in achieving organizational or company goals. The purpose of human resource management is to become a resource that has a competitive advantage through human resource management, which includes making the right decisions and managing environmental changes such as technology, business restructuring, competitors, and social and legal politics. If all aspects are managed by superior human resources, an organization or company can achieve its goals effectively and efficiently.